2016
DOI: 10.1007/s10585-016-9811-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequent co-expression of EGFR and NeuGcGM3 ganglioside in cancer: it’s potential therapeutic implications

Abstract: Interaction between epidermal growth factor receptor (EGFR) signaling with GM3 ganglioside expression has been previously described. However, little is known about EGFR and NeuGcGM3 co-expression in cancer patients and their therapeutic implications. In this paper, we evaluate the co-expression of EGFR and NeuGcGM3 ganglioside in tumors from 92 patients and in two spontaneous lung metastasis models of mice (Lewis lung carcinoma (3LL-D122) in C57BL/6 and mammary carcinoma (4T1) in BALB/c). As results, co-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…EGFR and NGcGM3 ganglioside are molecules co-expressed on spontaneous lung metastases induced by 3LL-D122 or 4T1-clones [ 28 ]. Interestingly in the 3LL-model, NGcGM3 expression increases progressively from the primary tumor to the lung metastasis [ 29 ], being almost inexistent on the tumor cells when cultured in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…EGFR and NGcGM3 ganglioside are molecules co-expressed on spontaneous lung metastases induced by 3LL-D122 or 4T1-clones [ 28 ]. Interestingly in the 3LL-model, NGcGM3 expression increases progressively from the primary tumor to the lung metastasis [ 29 ], being almost inexistent on the tumor cells when cultured in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we substituted the ganglioside vaccine for a passive therapy with the 14F7 mAb, which is specific for NGcGM3 ganglioside [ 32 ]. Previously, we reported that the combination therapy using the mAbs 7A7 and 14F7 increases the overall survival on the models of experimental lung metastasis of 3LL-D122 [ 28 ]. Here we further evaluated this combination of passive therapies, but in the spontaneous lung metastasis model (3LL-D122-cells) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NeuGcGM3, because of its selective expression in tumors, is a potentially useful target for immunotherapy, e.g., using Racotumomab-alum vaccine ( Alfonso et al, 2014 ) or recombinant monoclonal antibody 14F7 ( Piperno et al, 2015 ). In cases in which NeuGcGM3 and EGFR are involved jointly in tumor cell metastasis, therapeutic strategies that simultaneously target both molecules may be effective ( Palomo et al, 2016 ).…”
Section: Lung Cancermentioning
confidence: 99%